Influência do tratamento de superfície na rugosidade e na alteração de cor de duas cerâmicas odontológicas - Maciel, Lucas Campagnaro (2016)
Statement of the Problem: Corrections are commom step to adapt clinically and aesthetically ceramic piece, resulting in loss of gloss and surface smoothness achieved by the glaze, which may cause discoloration of these materials. Purpose: To evaluate the effect of superficial treatment on the surface roughness and the color change of the glass-ceramics pressed and veenered after immersed in coffee solution. Material and Methods: 88 ceramic discs were made (1.0 mm x 10.0 mm) according to the manufacturer’s recommendations. Where, 44 were pressed glass-ceramic (Group P) and 44 glass-ceramic veneered (Group C). Groups were divided into four subgroups according to the surface treatment: (G) Glaze, (S) polishing kit Shofu Inc, (E) polishing kit Edenta AG, (KG) diamond rotatory instrument 30 pm. Surface roughness (Ra) tests were performed after surface treatment and color change (AE) before and after 12 days after immersion in coffee solution. A qualitative analysis of the surface of the specimens was made with scanning electron microscopy. Data were statistically analyzed with ANOVA 1 factor and Duncan, further the paired t-test and Pearson correlation (a = 5%). Results: The ascending order for both surface roughness (Ra) and AE for both ceramics were: G < S < E < KG. Except subgroups PG and VG that showed no statistically significant difference each other, all other subgroups of pressed ceramic showed lower values of Ra and higher AE values than the veneering porcelain. Conclusion: The change of color of dental ceramics can be influenced by the surface roughness, and there is a strong correlation between surface roughness and color change of the tested ceramics.